2015
DOI: 10.1097/iae.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Outer Retinal Tubulation in Advanced Age-Related Macular Degeneration

Abstract: Purpose To compare optical coherence tomography (OCT) and histology of outer retinal tubulation (ORT) secondary to advanced age-related macular degeneration (AMD) in patients and in post-mortem specimens, with particular attention to the basis of the hyper-reflective border of ORT. Method A private referral practice (imaging) and an academic research laboratory (histology) collaborated on two retrospective case series. High-resolution OCT raster scans of 43 eyes (34 patients) manifesting ORT secondary to adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 54 publications
(63 reference statements)
3
95
0
Order By: Relevance
“…14 The RPE loss exceeded the EZ loss in nearly all eyes, and ORTs consistently extended beyond the margins of preserved RPE. In more advanced cases, as measured by ERG response, ORTs were more numerous and longer.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…14 The RPE loss exceeded the EZ loss in nearly all eyes, and ORTs consistently extended beyond the margins of preserved RPE. In more advanced cases, as measured by ERG response, ORTs were more numerous and longer.…”
Section: Discussionmentioning
confidence: 89%
“…In the en face perspective, the ORT is characterized by an outer hyporeflective band that originates with photoreceptor cell nuclei, adjacent to a hyperreflective line that likely originates with the external limiting membrane and inwardly migrating inner segment mitochondria. 14 …”
Section: Discussionmentioning
confidence: 99%
“…The relative contributions of scattering and waveguiding in photoreceptors can be tested with outer retinal tubulation (ORT), a neurodegeneration and gliosis commonly found in macula of advanced AMD 2226 and some inherited retinal diseases. 22,2729 ORT contains degenerating long- and middle-wavelength-sensitive cones 30 pointing into a lumen encircled by the ELM, which is formed with Müller cells.…”
Section: Introductionmentioning
confidence: 99%
“…22,2729 ORT contains degenerating long- and middle-wavelength-sensitive cones 30 pointing into a lumen encircled by the ELM, which is formed with Müller cells. 26,31 ORT cones degenerate by OS loss, IS shrinkage, and mitochondrial fission and migration within the IS, leaving an ELM circle lacking photoreceptors at the end-stage. 26,32 On SD-OCT B-scan, ORT is identified as a hyperreflective circular or ovoid profile with a hyporeflective lumen, located in the outer nuclear layer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent clinicopathological findings showed that the ORT reflective border represents the mitochondria within degenerated inner segments (IS) translocated internally to the external limiting membrane (ELM), without the presence of outer segments [15, 16]. …”
Section: Discussionmentioning
confidence: 99%